Extraction of bioactive compound from pulp and roots of benincasa hispida a.k.a. kundur - Mohd Khairul Anwar, Md Nor (2013)
This research was about the extraction of bioactive compound in pulp and roots of Benincasa hispida. The objective was to investigate bioactive compound (riboflavin) presence in the pulp and roots of Benincasa hispida aka kundur. The pulp was grind to supernatant juices. The juices were dried under the sunlight. As for the roots, it was also be cut into small pieces after been dry under the sunlight. Both of the samples then were undergoing the soxhlet extractor. Three different types of solvents were used, that are ultra pure water, methanol, ethanol. Both methanol and ethanol was prepared with three different concentrations which are 30%, 40% and 50%. After the samples undergo the soxhlet extractor, the samples then was undergo the rotary evaporator for separation of water from solvent. For data analysis, High Performance Liquid Chromatography (HPLC) were used as it shows accuracy more than other analysis methods. The HPLC will be use with C18 column. The concentrations also were determined by using HPLC. The result showed that methanol (40%) extracted more compare to the other solvents. For the roots, it can be said that there is no riboflavin detected. This research has the potential to be commercialized if appropriate time was given to do for more research and findings whereby the extracts of riboflavin can be sold at a high price and be used in medicinal field and food industry